Duties under the Principle of Respect for Dignity in the Context of Perinatal Loss - Margarita Boladeras-Cucurella (Universitat de Barcelona, 2024)
This research presents a conceptual analysis of the term «dignity», especially in its application in the context of perinatal loss issues, where it must be a moral guide for the necessary practices to address the problem. These practices can also be regulated by laws and professional guidance, so three laws in force in Argentina, Chile, and Colombia, as well as three Spanish professional action guides for these cases, are presented and analyzed. Based on all this, some conclusions are proposed. Objectives. Determine the moral obligations that arise from the principle of respect for human dignity in the field of professional practice of perinatal loss. Show the relationship that exists between the concepts of dignity, autonomy, integrity (physical and moral) and inviolability. Analyze and disclose the legal obligations established in some countries. Make known some existing professional practice guides in Spain on this subject. Material and method. Bibliographic search, analysis and hermeneutics of philosophical, legal, and professional deontological texts related to issues to perinatal loss. Conclusions. Guidelines on the best ways of professional action in situations of perinatal loss.